Governance Improvement of Cooperative: The Case of KUD Selikur Makmur Jambi - Arum, Enggar Diah Puspa; Wahyudi, Ilham; Wijaya, Rico; Wiralestari, Wiralestari; Brilliant, Aulia Beatrice (Jurnal Pengabdian Masyarakat Bestari, 2024)
The failure of organizations to implement governance effectively allows for various problems, including fraud, that have the potential to bring the organization to destruction. One case of ineffective cooperative governance occurred at KUD Selikur Makmur located in South Bahar District, Muaro Jambi Regency, Jambi Province. The purpose of this community service is to assist KUD Selikur Makmur in improving its governance and financial management. The Plan Do Check Act (PDCA) method, which is divided into three stages-preparation, implementation, and evaluation-was used to carry out the activities. This community service activity resulted in a governance model for KUD Selikur Makmur and improved the knowledge and skills of financial staff in carrying out their activities.